2011
DOI: 10.1149/2.041112jes
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Enhanced Cu Oxidation on Ruthenium∕Diffusion Barrier Layers for Cu Interconnects by Carbon Alloying into Ru

Abstract: The inhibition of Cu oxidation by alloying C into the Ru/TaN barrier stack is investigated. By using in-situ XRD measurement, severe copper oxide formation was observed for the Cu/Ru/barrier system during annealing process in He atmosphere. This phenomenon is explained using thermodynamics from the viewpoint of Gibbs free energy of oxide formation. The Cu oxidation can be inhibited by alloying C into the Ru layer, and the more C content in the RuC layer, the more evident the inhibition effect. The RuC/TaN stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…It is possible that a reduction of Cu oxidation takes place due to presence of RuC. This observation is consistence with the inhibition of Cu oxidation by C alloyed Ru reported by Ding et al [40]. The reduction of Cu 2 O was attributed to the effect of RuC layer, as the C doped in Ru capturing the O atom from Cu-O to form CO molecules.…”
Section: Surface Oxidation Behaviour Of Sintered Samplessupporting
confidence: 75%
See 3 more Smart Citations
“…It is possible that a reduction of Cu oxidation takes place due to presence of RuC. This observation is consistence with the inhibition of Cu oxidation by C alloyed Ru reported by Ding et al [40]. The reduction of Cu 2 O was attributed to the effect of RuC layer, as the C doped in Ru capturing the O atom from Cu-O to form CO molecules.…”
Section: Surface Oxidation Behaviour Of Sintered Samplessupporting
confidence: 75%
“…The high density value obtained in Cu-2 vol%CNT could be attributed to good dispersion of CNTs in Cu matrix. Moreover, this high densification showed that the potential sources of CNTs agglomeration that deteriorate metal-CNT composites density can be avoided by appropriate mixing process and sintering technique [19]. However, a reduction in density was observed in Cu-CNT composites containing 0.5 vol%Ru sintered at 600 C. This reduction could be due to insufficient sintering temperature since Ru has melting point of 2334 C. In addition, the Cu-CNT composites containing 0.5 vol%Ru was found to increase with increasing sintering temperature.…”
Section: Influence Of Densification On Microhardness Of Sintered Matementioning
confidence: 97%
See 2 more Smart Citations
“…The densification behaviour of the mixed powder was explained through the consideration of the shrinkage displacement and sintering time at different holding temperature during consolidation process [18,19].…”
Section: Sintering Behaviours Of the Mixed Powders During Spark Plasmmentioning
confidence: 99%